PENGARUH STRES KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DENGAN EMPLOYEE ENGAGEMENT SEBAGAI INTERVENING - Muhammad Ramadhan; Moch. Sarif Hasyim; Doni Mardiyanto (ITB AAS Indonesia Surakarta, 2026)
In modern organizations, human resources, specifically the people within an organization, are one of the primary means of creating competitive advantage, as the way we manage people directly impacts their performance. One of the critical challenges facing leaders is how to improve employee performance. This study aims to determine the effect of work stress and work discipline on employee performance, using Employee Engagement as an intervention for employees at the Directorate of Binalemlatvok, Ministry of Manpower, using a sample of 60 employees. Data analysis methods used descriptive analysis and SEM-PLS analysis with the assistance of SmartPLS 4.0 software. The results of the hypothesis testing prove: Work stress does not affect employee performance. Work discipline has a positive and significant effect on employee performance. Work stress has a negative and significant effect on employee engagement. Work discipline has a positive and significant effect on employee engagement. Employee engagement has a positive and significant effect on employee performance. Work stress does not affect employee performance through employee engagement. Work discipline affects employee performance through employee engagement. Keywords: Work Stress, Work Discipline, Employee Engagement, Employee Performance